Accounts and Accountability in Late Medieval Europe Records, Procedures, and Socio-Political Impact - Epurescu-Pascovici, Ionuț (UTRECHT STUDIES IN MEDIEVAL LITERACY, 2020)
This volume stems from a conference organised in November 2018 at the University of Bucharest in the frame of the European Research Council project CASTELLANY ACCOUNTS, "Record-keeping, fiscal reform, and the rise of institutional accountability in late-medieval Savoy: A source-oriented approach". Both the conference and the volume have received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (grant agreement No. 638436). The volume traces the momentous transformation of institutions and administration under the impact of accounting records and procedures, c. 1250-1500. The focus on the materiality and organising logic of a range of accounts is complemented by close attention to the socio-political contexts in which they functioned and the agency of central and local officials.